Conservation ecology of dragonflies (Odonata) in the Kogelberg Biosphere Reserve, a global biodiversity hotspot - Grant, Paul Brian Charles (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2005.